MANAGEMENT OF ORAL LICHEN PLANUS TRIGGERED BY STRESS : PENATALAKSANAAN ORAL LICHEN PLANUS PADA RONGGA MULUT - IGN Putra Dermawan; I Nyoman Gede Juwita Putra (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2021)
Introduction: Oral lichen planus (OLP) is a mucocutaneous disorder that rarely occurs around us and only involves the layer of the stratified squamous epithelium. Oral lichen planus is more common in women aged 30 - 65 years. The etiology of this disorder is not yet known, but there are severe predisposing factors that play a role,such as hepatitis C virus infection, food, drugs, malignancy and psychological factors. Purpose: This case report aims to describe the treatment of stress induced OLP. Case Report: A 46 year old man presented with complaints of stinging on the inner right and left cheeks for one month ago. The patient admits that he has a lot of thoughts related to family problems. It is found that the lesion resembles a white streak withredness that forms in the intraoral area. Case management: The patient was given therapy in the form of topical corticosteroids and consulted to psychiatry and got improvement after 1 week of treatment. Discussion: The treatment of OLP lesions is a treatment that requires collaboration between the dentist, the patient and the patient's family. Corticosteroid therapy is the gold standard treatment given to people with OLP. Corticosteroids are widely used in medicine because of their strong effect and fast anti-inflammatory reaction. Corticosteroids are widely used for the management of inflammatory diseases. Besides supporting therapy in consultation with a psychologist or psychiatrist to deal with stress disorders. Conclusion: Treatment of OLP lesions is a complex treatment. Corticosteroid therapy, both topical and systemic, is the most appropriate therapy and the role of a psychologist or psychiatrist is needed in managing patient stress to increase the percentage of patient recovery.